Signalling inhibition by ponatinib disrupts productive alternative lengthening of telomeres (ALT) - Kusuma, Frances Karla (2023)
Alternative lengthening of telomeres (ALT) supports telomere maintenance in 10-15% of cancers, thus representing a compelling target for therapy. By performing anti-cancer compound library screen on isogenic cell lines and using extrachromosomal telomeric C-circles, as a bona fide marker of ALT activity, we identify a receptor tyrosine kinase inhibitor ponatinib that deregulates ALT mechanisms, induces telomeric dysfunction, reduced ALT-associated telomere synthesis, and targets, in vivo, ALT-positive cells. Using RNA-sequencing and quantitative phosphoproteomic analyses, combined with C-circle level assessment, we find an ABL1-JNK-JUN signalling circuit to be inhibited by ponatinib and to have a role in suppressing telomeric C-circles. Furthermore, transcriptome and interactome analyses suggest a role of JUN in DNA damage repair. These results are corroborated by synergistic drug interactions between ponatinib and either DNA synthesis or repair inhibitors, such as triciribine. Taken together, we describe here a signalling pathway impacting ALT which can be targeted by a clinically approved drug.